Contemporary graphic design = Grafikdesign der Gegenwart Le graphisme contemporain - Fiell, Charlotte; Fiell, Peter (Taschen Books, 2010)
A compendium that showcases the extraordinary work of 100 of the world's most progressive graphic designers, from the hard-hitting political messages of Jonathan Barnbrook to the lyrical digital compositions of Peter Saville to the iconoclastic imagery of Stefan Sagmeister.